Implications of a food system approach for policy agenda-setting design - Kugelberg, Susanna (Glob Food Sec, 2021)
A call to governments to enact a strategy for a sustainable food system is high on the global agenda. A sustainable food system presupposes a need to go beyond a view of the food system as linear and narrow, to comprehend the food system as dynamic and interlinked, which involves understanding social, economic and ecological outcomes and feedbacks of the system. As such, it should be accompanied by strategic, collaborative, transparent, inclusive, and reflexive agenda-setting process. The concepts of, directionality relating to an agreed vision for a future sustainable food system, and, reflexivity which describes the capacity for critical deliberation and responsiveness, are particularly important. Based on those concepts, this paper proposes an evaluative framework to assess tools and instruments applied during the agenda-setting stage. We apply the evaluative framework to recent food policy processes in Finland and Sweden, revealing that their agenda-setting design cannot be assessed as fully addressing both directionality and reflexivity, thus possibly falling short of the policy design needed for enable more transformative policy approaches.